Corticosteroid-free efficacy and safety outcomes in patients receiving tofacitinib in the OCTAVE Sustain maintenance study. (May 2022) - Vavricka, Stephan R.; Greuter, Thomas; Cohen, Benjamin L.; Reinisch, Walter; Steinwurz, Flavio; Fellmann, Marc; Guo, Xiang; Lawendy, Nervin; Paulissen, Jerome; Peyrin-Biroulet, Laurent
Background: Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis (UC). Here, we report steroid-free efficacy and safety with tofacitinib among patients with UC who received corticosteroids at baseline of the maintenance study (OCTAVE Sustain). Methods: This analysis included patients with clinical response following OCTAVE Induction 1 and 2 who were re-randomized to receive placebo, or tofacitinib 5 or 10 mg twice daily (b.d.), in OCTAVE Sustain for 52 weeks and were receiving corticosteroids at OCTAVE Sustain baseline. Corticosteroid tapering was mandatory during OCTAVE Sustain. Rates of steroid-free remission, endoscopic improvement, and clinical response were assessed, stratified by baseline characteristics. Adverse events (AEs) were stratified by treatment and steroid-free remission status. Results: Overall, 289/593 patients had corticosteroid use at OCTAVE Sustain baseline. At week 52, steroid-free remission, endoscopic improvement, and clinical response rates were 10.9%, 11.9%, and 17.8% among patients receiving placebo, 27.7%, 29.7%, and 40.6% among patients receiving tofacitinib 5 mg b.d., and 27.6%, 29.9%, and 43.7% among patients receiving tofacitinib 10 mg b.d., respectively (non-responder imputation; all p  < 0.05 tofacitinib 5 or 10 mg b.d. versus placebo). Discontinuations due to AEs were lower among patients with steroid-free remission versus without. AEs of special interest were infrequent. Conclusion: For patients with baseline corticosteroid use in OCTAVE Sustain, the odds of achieving steroid-free efficacy endpoints were significantly higher for tofacitinib versus placebo, irrespective of tofacitinib dose. There were no apparent differences in AEs of special interest by steroid-free remission status. ClinicalTrials.gov: NCT01458574